2006
DOI: 10.1021/la0531953
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Size Selection in Cholesteric and Nematic Emulsions

Abstract: We study the spontaneous size selection in lyotropic cholesteric (W/O) and thermotropic nematic (O/W) liquid crystal emulsions. The droplet sizes have been characterized by dynamic light scattering, which indicates a narrow monomodal distribution of droplets achieved spontaneously even without emulsion filtration. Anchoring of the director, provided by the chosen surfactant on the interface, may generate a topological defect inside the droplet. Below the critical radius R = K/W, determined by the ratio of Fran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 18 publications
0
51
0
Order By: Relevance
“…NTA has previously been accurately used to size various nanomaterials including polymeric and metal nanoparticles, micelles, emulsions, viruses, and other colloids. 22−26 NTA is a more accurate sizing technique than DLS when polydisperse samples are used because the motion of individual particles is tracked. Although DLS does not track individual particles, it does evaluate light scattering from particles in a sample simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…NTA has previously been accurately used to size various nanomaterials including polymeric and metal nanoparticles, micelles, emulsions, viruses, and other colloids. 22−26 NTA is a more accurate sizing technique than DLS when polydisperse samples are used because the motion of individual particles is tracked. Although DLS does not track individual particles, it does evaluate light scattering from particles in a sample simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Emulsion droplets can be prepared by various techniques, such as photopolymerization [91], ultrasonication [92], shearing of droplets and subsequent crystallization fractionation [93, 94], droplet break-off in a co-flowing stream (microfluidics) [95], and dispersion polymerization [91, 96, 97]. However, the majority of these methods do not permit control over LC droplet size in the range that is optimal for LC sensing (1-10 μm, see below).…”
Section: Lc-in-water Emulsions As Sensorsmentioning
confidence: 99%
“…First, by using the above-described polymer templating method to fabricate water-dispersed PEM-coated 5CB droplets of a controlled size, Gupta et al [80] demonstrated that decreasing the size of the LC droplets led to spontaneous bipolar-to-radial ordering transitions below a critical droplet diameter of approximately 800 nm (R ≈ 400 nm) (Figure 17C-M). Although many theoretical scaling arguments predicted the size-dependent stability of director configurations within LC droplets [92, 100, 101], these arguments generally predict a spontaneous transition to a uniform director configuration within sub-micrometer sized LC droplets (Figure 17A and B) rather than a transition to the radial configuration. Gupta et al [80] also showed that the sensitivity of LC droplets which undergo a bipolar-to-radial ordering transition in the presence of interfacial adsorbates can be adjusted by controlling the size of the droplets (Figure 17N).…”
Section: Lc-in-water Emulsions As Sensorsmentioning
confidence: 99%
“…22 In the experiment, 1 the abundance of surfactants may have reduced below W. For lyotropic nematics made of self-assembled molecular aggregates similar to worm-like micelles, W / Ͼ 1 has been observed for domains in a biphasic system. 20,23 The mechanism revealed by the heart-shaped bubble has potential applications in other complex fluids that feature nematic-isotropic interfaces, such as nematic emulsions 24 and polymer-dispersed liquid crystals ͑PDLC͒. 25 In selfassembly of colloids for making photonic crystals, 26 a nematic matrix will afford better control of the spatial periodicity as well as the possibility of nonspherical voids with better performance and tunability.…”
Section: Phys Fluids 19 041703 ͑2007͒mentioning
confidence: 99%